Dr. Seuss's sleep book - Seuss, Dr. (N. Y. : Harper Collins Children's Books, 1990)
Tells, in verse, what happens when all ninety-nine zillion nine trillion and three creatures in the world go to sleep.
Keywords: Stories in rhyme; Fantasy